Composite positive electrode material and preparation method and application thereof
Through capillary wet coating technology of liquid metal materials, the positive electrode material of sodium ion battery is completely coated, solving the problems of limited conductivity and uneven coating in the prior art, and achieving high conductivity and excellent Electrochemical properties significantly improve the cycle stability and rate performance of the material.
Patent Information
- Application Number
- CN202411305869.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The existing sodium ion battery positive electrode materials have shortcomings in terms of cycle stability and rate performance, especially due to the presence of the cladding layer, the conductivity is limited, and traditional cladding materials are difficult to completely coat primary particles, affecting the surface of the material. Modification effect.
Liquid metal material is used as a new type of coating material, and the layered transition metal oxide positive electrode material is coated through wet coating technology under capillary force to achieve complete coverage of primary and secondary particles, and improve the structural stability of the material. and conductivity.
It realizes that the sodium ion battery has high conductivity, excellent structural stability and electrochemical properties without the conductive agent. The discharge specific capacity of the first round reaches 148.69mAh·g-1, and the capacity retention rate reaches 98.96 after 300 rounds. %, significantly improves the cycle stability and rate performance of the material.
Smart Images

Figure CN119208557A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a composite positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles, consumer electronics, power supply systems, large-scale energy storage and other fields, people's demand for energy storage devices is increasing. As a star player in the field of energy storage, lithium-ion batteries have received widespread attention from all walks of life. However, with the over-exploitation of lithium resources, the price of lithium raw materials has risen sharply since 2021, and people have shifted their attention to sodium-ion batteries, which have a wide distribution of resources and low prices. Sodium-ion batteries work in a similar way to lithium-ion batteries, with the advantages of low cost, fast charging speed, high safety, and a wide temperature range, but there is still much room for improvement in terms of cycle life and energy density.
[0003] The positive electrode material is a key factor in determining the performance of sodium-ion batteries. Currently, common sodium positive electrode materials include transition metal oxide materials, polyanion materials, and Prussian blue materials. Compared with other positive electrode materials, layered transition metal oxide materials have open two-dimensional channels, high theoretical energy density, simple synthesis, and environmental friendliness, and have great development potential. However, due to the large ionic radius of sodium ions, such materials will undergo irreversible structural phase changes during the charge and discharge process, causing serious capacity decay. How to improve the cycle stability of the material is the focus of scientific researchers.
[0004] In the past, in order to improve the cycle stability of positive electrode materials under high voltage conditions, researchers have improved the interfacial stability of layered oxide positive electrode materials by constructing a protective layer on the surface of the electrode material. The coating layer can prevent the material from directly contacting the electrolyte, thereby inhibiting the occurrence of side reactions, forming a dense and thick CEI film, increasing the internal resistance of the battery, and hindering the Na + transmission; at the same time, it can inhibit the dissolution of transition metals, maintain the stability of the outer surface crystal structure, prevent electrolyte corrosion, and thus improve the cycle performance of the material.
[0005] CN118538903A discloses a surface-modified layered oxide sodium ion battery positive electrode material, the chemical formula of which is NaNi x Fe y Mn z O 2 @M a O b , where M a O b In the form of P-phase layered oxide coated on NaNi x Fe y Mnz O 2 This technical solution forms a more stable P-phase inert sodium-poor surface structure on the surface of the positive electrode particles, avoiding the dissolution of active transition metal elements during the cycle and the direct contact between high-valent active elements and the electrolyte in the charged state, catalyzing the decomposition of the electrolyte, inhibiting the degradation of the interface structure, solving the interface problem during the cycle, and effectively improving the long-cycle performance of the material.
[0006] CN115954445A discloses a nano sodium oxalate composite positive electrode active material and its application, wherein the nano sodium oxalate composite positive electrode active material is a sodium ion layered oxide coated with nano sodium oxalate, wherein the matrix is a sodium ion layered oxide, and the coating layer is nano sodium oxalate. This technical solution coats nano sodium oxalate on the surface of the sodium ion layered oxide, so that it has the advantages of sodium oxalate crystals themselves, and can also increase the utilization rate of sodium salt, so that no sodium supplement is needed when making batteries, which is beneficial to industrial development. The nano sodium oxalate composite positive electrode active material provided by this technical solution can increase the charging capacity of sodium ion batteries, achieve the positive electrode sodium supplement effect, and can also reduce the pH value of the product, improve the product processing performance, and increase the battery pole piece yield.
[0007] CN117219739A discloses a La 2 Zr 2 O 7 Coated layered oxide sodium ion battery positive electrode material and preparation method, the layered oxide sodium ion battery positive electrode material is an O3 or P2 phase layered positive electrode material, the chemical formula is Na x TMO y , the coating material is Pmma structure La 2 Zr 2 O 7 This technical solution uses a liquid phase method to coat the layered oxide sodium ion battery positive electrode material. The coating is comprehensive and uniform, which can effectively improve the electrochemical properties of the sodium ion positive electrode material, such as reversible capacity, rate performance, cycle life and initial coulombic efficiency.
[0008] Although the above research has modified the layered transition metal oxide positive electrode material by surface coating, improved the structural stability of the material, and enhanced the electrochemical properties such as the cycle life of the sodium ion battery, the conductivity of the material is limited due to the presence of the coating layer, and the rate performance of the material and the stability of the material under high pressure need to be further improved; in addition, traditional coating materials can usually only coat secondary particles, and it is difficult to achieve complete coating of primary particles, which seriously affects the surface modification effect of the material. Summary of the invention
[0009] In view of the problems existing in the prior art, the purpose of the present invention is to provide a composite positive electrode material and a preparation method and use thereof, wherein the composite positive electrode material comprises a core and a coating layer coated on the surface of the core, wherein the core comprises a layered transition metal oxide positive electrode material, and the coating layer comprises a liquid metal material. The coating layer formed by using a special liquid metal material as a new type of coating material can achieve complete coating of primary particles and secondary particles, effectively promote electron and charge transfer and structural stability, and hinder interface reactions; the sodium ion battery made of the composite positive electrode material still has high conductivity, excellent structural stability and electrochemical performance without the presence of a positive electrode conductive agent.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a composite positive electrode material, comprising a core and a coating layer coating the core, wherein the core comprises a layered transition metal oxide positive electrode material, and the coating layer comprises a liquid metal material.
[0012] The composite positive electrode material provided by the present invention is a composite of a layered transition metal oxide positive electrode material and a liquid metal material. The layered transition metal oxide positive electrode material is prone to irreversible structural phase change under high pressure, accompanied by dissolution of transition metal ions, interface side reactions, etc. Coating a layer of liquid metal material on the surface of the layered transition metal oxide positive electrode material can greatly improve the structural stability of the material; its high conductivity can make the composite positive electrode material show good rate performance without a conductive agent; in addition, the liquid metal material is a new type of coating material that can achieve efficient and complete coating of primary particles and secondary particles, thereby more effectively promoting the improvement of electron and charge transmission and structural stability, and hindering interface reactions; the sodium ion battery made of the composite positive electrode material still has high conductivity, excellent structural stability and electrochemical performance without a positive electrode conductive agent.
[0013] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0014] As a preferred technical solution of the present invention, the chemical formula of the layered transition metal oxide positive electrode material is Na x MO 2 , wherein M includes at least one of Fe, Ni, Co, Mn, and V, 0<x≤1, for example, x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc.
[0015] Preferably, M is a combination of Ni and Mn, and the chemical formula of the layered transition metal oxide positive electrode material is Na 0.67 Ni 0.33 Mn 0.67 O 2 .
[0016] Preferably, the layered transition metal oxide positive electrode material is a P2 phase.
[0017] As a preferred technical solution of the present invention, the liquid metal material includes at least one of nano-scale eutectic gallium indium (EGaIn), gallium indium tin nanoparticles (GaInSn) or gallium nanoparticles (Ga).
[0018] In the present invention, the liquid metal material is in liquid state at room temperature and pressure (melting point ≤ 30°C), can flow and deform like a liquid, has good structural deformability and high electronic conductivity, and the conductivity is preferably ≥10 6 S·m -1 .
[0019] Preferably, the mass ratio of the liquid metal material to the layered transition metal oxide positive electrode material is (0.01-0.5):1, for example, 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.1:1, 0.13:1, 0.15:1, 0.18:1, 0.2:1, 0.22:1, 0.25:1, 0.28:1, 0.3:1, 0.33:1, 0.35:1, 0.38:1, 0.4:1, 0.42:1, 0.45:1, 0.48:1 or 0.5:1, etc., and is further preferably (0.03-0.2):1.
[0020] In the present invention, if the coating amount of the liquid metal material is too much, it will easily affect the transmission of sodium ions and reduce the kinetic properties of the material; if the coating amount of the liquid metal material is too little, it will easily lead to uneven coating and low material conductivity, and the advantages of the coating material cannot be fully utilized.
[0021] In a second aspect, the present invention provides a method for preparing the composite positive electrode material according to the first aspect, the preparation method comprising:
[0022] The layered transition metal oxide material and the liquid metal material are mixed and dispersed in a medium solvent to obtain a composite positive electrode material capillary suspension, the composite positive electrode material capillary suspension is used to form an initial layer on a thin film material, and the film material is pressed to obtain a pressed body, and then the thin film material in the pressed body is peeled off to obtain a composite positive electrode material.
[0023] Existing surface coating modification technology mainly coats the secondary particles of positive electrode materials. When charged to high voltage, primary particles will be exposed. Primary particles that are not completely coated are easy to react with electrolytes to generate by-products, and will also cause transition metals to dissolve and structural collapse, thereby affecting material performance. In the present invention, the liquid metal material has a low melting point and excellent structural deformability. By selecting a suitable medium solvent as a dispersant, the capillary force can be used to overcome the surface tension of the liquid metal. The wet coating method can not only overcome the surface tension of the liquid metal and achieve complete surface coating of the secondary particles, but also achieve seamless injection and full coating of the primary particles, which can effectively isolate the direct contact between the positive electrode material and the electrolyte, inhibit the occurrence of interface side reactions and the dissolution of transition metals in the positive electrode material, and enhance the structural stability and cycle life of the material. In addition, traditional coating methods result in low conductivity of the coated positive electrode material, and dry coating will also lead to incomplete bonding between particles, resulting in poor conductivity of the material. When preparing a slurry containing both active materials and conductive agents, excess carbon components will reduce the proportion of active materials in the electrode, resulting in a decrease in the overall energy density and specific capacity of the battery. Liquid metal, as an excellent electronic conductor, can fully combine with primary and secondary particles, so that the composite material can still exhibit good conductivity without adding a conductive agent.
[0024] As a preferred technical solution of the present invention, the method for preparing the layered transition metal oxide material includes adding a chelating agent to a solution containing a sodium source and an M source to obtain a mixed solution, heating and stirring to obtain a sol, and drying and calcining the sol to obtain the layered transition metal oxide positive electrode material.
[0025] Preferably, the M source includes at least one of sulfate, chloride, acetate, nitrate or oxide of the M element.
[0026] Preferably, when the M source contains nickel element, the M source includes a nickel source, and the nickel source includes at least one of nickel chloride, nickel acetate, nickel nitrate, nickel sulfate or nickel oxide.
[0027] Preferably, when the M source contains manganese element, the M source includes a manganese source, and the manganese source includes at least one of manganese chloride, manganese acetate, manganese nitrate, manganese sulfate, manganese dioxide, manganese oxalate or potassium permanganate.
[0028] Preferably, the sodium source comprises at least one of sodium carbonate, sodium acetate, sodium nitrate or sodium hydroxide.
[0029] Preferably, the dissolving solvent of the solution containing the sodium source and the M source includes at least one of deionized water, ethanol or hydrogen peroxide, preferably deionized water.
[0030] Preferably, the chelating agent includes at least one of citric acid, ethylene glycol, and EDTA (ethylenediaminetetraacetic acid), preferably citric acid.
[0031] Preferably, the amount of the chelating agent and the solution containing the sodium source and the M source is controlled according to the ratio of the molar amount of the chelating agent to the total molar amount of the transition metal (0.5-1.5):1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, etc., preferably (0.8-1.2):1.
[0032] In the present invention, the purpose of using a chelating agent in the process of preparing a layered transition metal oxide positive electrode material is to form a uniform gel, stabilize metal ions, and improve the uniformity of the product. If the chelating agent content is too low, the gel network is likely to be unstable and incomplete, resulting in a loose structure of the positive electrode material and poor cycle stability; if the chelating agent content is too high, the gel network is likely to be too dense, so that the growth of the positive electrode material crystal is restricted, and it is difficult to form a uniform crystal structure in the subsequent heat treatment process, resulting in uneven particle size and increased grain boundaries. At the same time, the pore structure of the material is overfilled, affecting the Na + The storage sites and migration channels of the materials affect the capacity and rate performance.
[0033] Preferably, the heating temperature is 60-100°C, for example 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, etc., preferably 70-90°C.
[0034] Preferably, the stirring includes magnetic stirring and / or mechanical stirring; the rotation speed is 200-500rpm, for example 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm or 500rpm, etc., preferably 300-400rpm; the time is 2-6h, for example 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, etc., preferably 3-5h.
[0035] Preferably, the drying includes forced air drying and / or vacuum drying; the temperature is 100-200°C, for example 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc., preferably 140-160°C; the time is 4-8h, for example 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, etc., preferably 5-7h.
[0036] Preferably, the calcination comprises: -1Heating rate, for example 1℃·min -1 、2℃·min -1 、3℃·min -1 、4℃·min -1 、5℃·min -1 、6℃·min -1 、7℃·min -1 、8℃·min -1 、9℃·min -1 or 10℃·min -1 etc., firstly raise the temperature to 300-600°C, for example, 300°C, 330°C, 350°C, 380°C, 400°C, 430°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C or 600°C, etc., and perform the first sintering for 4-8h, for example, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, etc., and then raise the temperature to 700-1100°C, for example, 700°C, 730°C, 750°C, 780°C, 800°C, 820°C, 8 The second sintering is carried out at a temperature of 50°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, 1020°C, 1050°C, 1080°C or 1100°C for 10 to 20 hours, for example, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h or 20h.
[0037] Further preferably, the calcination comprises: -1 The heating rate is first raised to 400-500°C for the first sintering for 5-7h, and then raised to 850-950°C for the second sintering for 14-16h.
[0038] Preferably, the calcination atmosphere includes any one of air atmosphere, oxygen atmosphere or argon atmosphere, preferably air atmosphere.
[0039] In the present invention, if the calcination temperature is too low or the calcination time is too short, it is easy to cause the positive electrode material to be imperfectly crystallized and the distance between particles to be large, which will lead to Na + The diffusion path is long, which affects the kinetic properties of the material and is easy to generate impurities, which is not conducive to the formation of a pure phase structure, causing the material to exhibit a lower initial capacity and poor cycle stability; if the calcination temperature is too high or the calcination time is too long, and the distance between particles is too small, the particles are prone to agglomeration, resulting in Na + During the embedding and de-embedding process, the structure collapses, the capacity decays rapidly, and the cycle performance deteriorates.
[0040] As a preferred technical solution of the present invention, the preparation method comprises:
[0041] The medium solvent includes solvent A and solvent B, wherein the polarity indexes of solvent A and solvent B are different and immiscible; the liquid metal material is mixed and dispersed in solvent A, and subjected to water bath ultrasonic treatment to obtain a liquid metal solution; the obtained liquid metal solution and a layered transition metal oxide positive electrode material are mixed and dispersed in solvent B to obtain a capillary suspension of the composite positive electrode material;
[0042] Preferably, the absolute value of the difference in polarity index between the solvent A and the solvent B is ≥5, for example, 5, 5.3, 5.5, 5.8, 6, 6.2, 6.5, 6.8 or 7.
[0043] Preferably, both the solvent A and the solvent B have good chemical stability to the liquid metal material and the layered transition metal oxide positive electrode material; compared with the solvent B, the solvent A has poor compatibility with the liquid metal material and the layered transition metal oxide positive electrode material, and the solvent B has good compatibility with the liquid metal material and the layered transition metal oxide positive electrode material.
[0044] Preferably, the volume ratio of the solvent A to the solvent B is (6-12):1, preferably (8-10):1.
[0045] In the present invention, immiscible solvent A and solvent B can be mixed with each other to obtain a "capillary suspension" solution, which appears to be a small amount of solvent B suspended in a large amount of solvent A. Liquid metal materials and layered transition metal oxide positive electrode materials can be well dispersed in solvent B but not in solvent A. As a result, the two types of materials are connected by a capillary bridge formed by solvent B. Since liquid metal has excellent structural deformability, after medium solvent drying and high temperature and high pressure pressing, the uniformly coated composite positive electrode material can be obtained.
[0046] Preferably, the solvent A includes at least one of dodecane, hexane or octanol; preferably dodecane.
[0047] Preferably, a surfactant is also added to the solvent A, and the surfactant includes AOT (sodium di(2-ethylhexyl)sulfosuccinate), and the surfactant accounts for 0.8% to 1.2% of the mass of the solvent A, for example, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15% or 1.2%, etc., preferably 1%.
[0048] In the present invention, the addition of AOT can improve the dispersibility of the solution and prevent the particles from agglomerating.
[0049] Preferably, the solvent B comprises at least one of methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or water, preferably methylpyrrolidone.
[0050] Preferably, the combination of the solvent A and the solvent B is preferably a combination of Dodecane and NMP, or a combination of Dodecane and DMF.
[0051] Preferably, the water bath ultrasound treatment time is 0.2 to 0.8 h, for example, 0.2 h, 0.25 h, 0.3 h, 0.35 h, 0.4 h, 0.45 h, 0.5 h, 0.55 h, 0.6 h, 0.65 h, 0.7 h, 0.75 h or 0.8 h, etc., preferably 0.4 to 0.6 h.
[0052] Preferably, the mixing and dispersing device comprises a planetary mixer.
[0053] Preferably, the mixing and dispersing rotation speed is 100-300 rpm, for example, 100 rpm, 130 rpm, 150 rpm, 180 rpm, 200 rpm, 220 rpm, 250 rpm, 280 rpm or 300 rpm, and the mixing and dispersing time is 2-6 h, for example, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h, etc.
[0054] Preferably, the film material comprises at least one of PET, PE, PP or PPS, preferably PET.
[0055] Preferably, the pressing temperature is 80-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, and the pressure is 12-18MPa, for example, 12MPa, 12.5MPa, 13MPa, 13.5MPa, 14MPa, 14.5MPa, 15MPa, 15.5MPa, 16MPa, 16.5MPa, 17MPa, 17.5MPa or 18MPa, etc.
[0056] Preferably, the pressed body is cooled first and then the peeling is performed.
[0057] Preferably, the cooling temperature is 0-10°C, for example, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C or 10°C, and the cooling time is 0.5-2h, for example, 0.5h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2h, etc.
[0058] In a third aspect, the present invention provides a positive electrode plate, comprising a current collector and an active layer disposed on the current collector, wherein the active layer comprises the composite positive electrode material described in the first aspect and a binder, and does not contain a conductive agent.
[0059] Preferably, the binder comprises PVDF.
[0060] Preferably, the mass ratio of the composite positive electrode material to the binder is (8.8-9.2):1, for example, 8.8:1, 8.85:1, 8.9:1, 8.95:1, 9:1, 9.05:1, 9.1:1, 9.15:1 or 9.2:1, etc., preferably 9:1.
[0061] Preferably, the current collector comprises aluminum foil.
[0062] In a fourth aspect, the present invention provides a method for manufacturing the positive electrode sheet described in the third aspect, the manufacturing method comprising: mixing the composite positive electrode material, a binder and a pulping solvent to obtain a slurry, coating the obtained slurry on a current collector, and slicing after drying to obtain a positive electrode sheet.
[0063] Preferably, the pulping solvent comprises NMP.
[0064] Preferably, the drying comprises drying in a forced air dryer at 40-80°C, for example, 40°C, 50°C, 60°C, 70°C or 80°C, for 1-3h, for example, 1h, 1.5h, 2h, 2.5h or 3h, etc., and then transferring to a vacuum dryer at 100-140°C, for example, 100°C, 110°C, 120°C, 130°C or 140°C, for drying for 8-16h, for example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h, etc.
[0065] Preferably, the mass loading of the composite cathode material on the current collector is 1.5-1.8 mg / cm 2 , for example 1.5 mg / cm 2 、1.55mg / cm 2 、1.6mg / cm 2 、1.65mg / cm 2 , 1.7mg / cm 2 、1.75mg / cm 2 or 1.8 mg / cm 2 Etc., that is, the mass of the composite positive electrode material carried on each square centimeter of the electrode.
[0066] In a fifth aspect, the present invention provides a sodium ion battery, comprising the positive electrode plate described in the third aspect, as well as an electrolyte, a separator and a negative electrode plate.
[0067] Preferably, the diameter of the positive electrode plate is 10-12 mm, for example, 10 mm, 10.5 mm, 11 mm, 11.5 mm or 12 mm.
[0068] Preferably, the electrolyte comprises 1M NaClO 4 It is dissolved in propylene carbonate, and 4% to 6% of fluoroethylene carbonate (FEC) is added as an additive, for example, 4%, 4.5%, 5%, 5.5% or 6%, preferably 5%.
[0069] Preferably, the diaphragm comprises a glass fiber diaphragm; the diameter of the diaphragm is 16-18 mm, for example, 16 mm, 16.5 mm, 17 mm, 17.5 mm or 18 mm.
[0070] Preferably, the negative electrode plate comprises a metallic sodium negative electrode plate; the diameter of the negative electrode plate is 12 to 14 mm, for example, 12 mm, 12.5 mm, 13 mm, 13.5 mm or 14 mm.
[0071] In a sixth aspect, the present invention provides a power device, comprising the sodium ion battery described in the fifth aspect.
[0072] It should be noted that due to space limitations and to avoid redundancy, the present invention does not exhaustively list all point values within the above numerical range, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0073] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0074] (1) The composite positive electrode material provided by the present invention has excellent structural stability, electrical conductivity and good rate performance. On the one hand, by using a new coating material, liquid metal material, complete coating of primary particles and secondary particles can be achieved, which can inhibit the interfacial reaction between the positive electrode material and the electrolyte, hinder the formation of a solid electrolyte interface film, and avoid the impact of adverse interfacial reactions on sodium ion migration; on the other hand, the high conductivity of the liquid metal material realizes the preparation of conductive agent-free positive electrode sheets, avoiding capacity loss due to low active material content. The resulting sodium ion battery has good cycle stability, high initial capacity and excellent rate performance. The composite positive electrode material provided by the present invention has a first-cycle discharge specific capacity of up to 148.69 mAh·g at a charge and discharge rate of 0.1C. -1 After 300 cycles, the discharge capacity is 147.14 mAh g -1 , the capacity retention rate reached 98.96%.
[0075] (2) The composite cathode material preparation method provided by the present invention performs wet coating under capillary force, which can not only overcome the surface tension of liquid metal and achieve efficient coating of secondary particles, but also fully coat primary particles, effectively avoiding the dissolution of transition metal ions and the side reactions caused by direct contact between the composite cathode material and the electrolyte, greatly improving the structural stability of the material. The composite cathode material preparation method is simple to operate, has a short process, low cost, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 It is a schematic diagram of the material change process in the preparation method of the composite positive electrode material of Example 1. DETAILED DESCRIPTION
[0077] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0078] The following are typical but non-limiting embodiments of the present invention:
[0079] Example 1
[0080] This embodiment provides a composite positive electrode material, the composite positive electrode material includes a core and a coating layer covering the core, the core includes a layered transition metal oxide positive electrode material, the coating layer includes a liquid metal material; the chemical formula of the layered transition metal oxide positive electrode material is Na 0.67 Ni 0.33 Mn 0.67 O 2 , belongs to the P2 phase, denoted as P2-Na 0.67 Ni 0.33 Mn 0.67 O 2 , abbreviated as NNMO; the liquid metal material is nano-scale eutectic gallium indium (EGaIn) with excellent structural deformability and high electronic conductivity; the mass ratio of the liquid metal material to the layered transition metal oxide positive electrode material is 0.05:1;
[0081] The preparation method of the composite positive electrode material comprises:
[0082] (1) Preparation of layered transition metal oxide positive electrode materials using the sol-gel method:
[0083] According to the molecular formula P2-Na 0.67 Ni 0.33 Mn 0.67 O 2 , that is, the stoichiometric ratio is 0.72:0.33:0.67. Weigh the corresponding mass of anhydrous sodium acetate (CH3 COONa), nickel source nickel acetate tetrahydrate (Ni(CH 3 COO 2 ·4H 2 O) and manganese source manganese acetate tetrahydrate (Mn(CH 3 COO 2 ·4H 2 O), and adjust the sodium source to an excess of 5wt% to compensate for the sodium loss during high-temperature calcination, dissolve it in 50mL of deionized water, and stir it magnetically at 400rpm in a beaker for 30min. After mixing evenly, an initial metal solution is obtained; the obtained initial metal solution is dissolved in a certain amount of anhydrous citric acid solution, wherein the ratio of the molar amount of anhydrous citric acid to the total molar amount of transition metals in the initial metal solution is 1:1, to obtain a mixed solution; the obtained mixed solution is heated in an 80°C water bath and maintained at 350rpm magnetic stirring until a wet gel appears, and the obtained wet gel is dried in an oven at 150°C for 6h to obtain a dry gel, which is a precursor. After the obtained precursor is fully ground, it is sintered at 5°C·min in an air atmosphere. -1 The temperature was raised to 450℃ for pre-sintering (first sintering) for 6h, and then heated at 5℃·min in air atmosphere. -1 After heating to 900°C and calcining (second sintering) for 15 hours, the layered transition metal oxide positive electrode material P2-Na 0.67 Ni 0.33 Mn 0.67 O 2 .
[0084] (2) Preparation of composite cathode materials by wet coating under capillary force:
[0085] EGaIn was added to 9 ml of Dodecane (solvent A) containing 1 wt.% AOT and mixed and dispersed, and then the mixture was subjected to water bath ultrasonic treatment for 0.5 h to obtain EGaIn-Dodecane solution (liquid metal solution). 0.67 Ni 0.33 Mn 0.67 O 2 and 1 ml of NMP (solvent B) using a planetary mixer at a rotation speed of 200 rpm for 4 hours to obtain a capillary suspension of a composite positive electrode material. The capillary suspension of the composite positive electrode material is cast on a thin film material PET using a scraper to form an initial layer, and then pressed at 100°C at a pressure of 15 MPa to obtain the composite positive electrode material.
[0086] Example 2
[0087] This embodiment provides a composite positive electrode material, in which the liquid metal material is replaced by nano-scale eutectic gallium indium (EGaIn) with gallium indium tin nanoparticles (GaInSn). Except for the above, other conditions are exactly the same as those in Example 1.
[0088] Example 3
[0089] This embodiment provides a composite positive electrode material, in which the liquid metal material is replaced by nano-scale eutectic gallium indium (EGaIn) with gallium nanoparticles (Ga). Except for the above, other conditions are exactly the same as those in Example 1.
[0090] Example 4
[0091] This embodiment provides a composite positive electrode material. In the preparation method of the composite positive electrode material, in step (2), solvent A is replaced by Octanol from Dodecane. Except for the above, other conditions are exactly the same as those in Example 1.
[0092] Example 5
[0093] This embodiment provides a composite positive electrode material. In the preparation method of the composite positive electrode material, in step (2), solvent B is replaced by DMF from NMP. Except for the above, other conditions are exactly the same as those in Example 1.
[0094] Example 6
[0095] This embodiment provides a composite positive electrode material, in which the mass ratio of the liquid metal material to the layered transition metal oxide positive electrode material is adjusted from 0.05:1 to 0.03:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0096] Example 7
[0097] This embodiment provides a composite positive electrode material, in which the mass ratio of the liquid metal material to the layered transition metal oxide positive electrode material is adjusted from 0.05:1 to 0.2:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0098] Example 8
[0099] This embodiment provides a composite positive electrode material, in which the volume ratio of solvent A to solvent B is adjusted from 9:1 to 8:1. Except for the above, other conditions are exactly the same as those in Embodiment 1.
[0100] Example 9
[0101] This embodiment provides a composite positive electrode material, in which the volume ratio of solvent A to solvent B is adjusted from 9:1 to 10:1. Except for the above, other conditions are exactly the same as those in Embodiment 1.
[0102] Example 10
[0103] This embodiment provides a composite positive electrode material. In the preparation method of the composite positive electrode material, in step (2), solvent A is replaced by NMP from Dodecane. Except for the above, other conditions are exactly the same as those in Example 1.
[0104] Comparative Example 1
[0105] This comparative example uses the layered transition metal oxide positive electrode material obtained in step (1) of Example 1 for subsequent testing.
[0106] Comparative Example 2
[0107] This comparative example provides a composite positive electrode material, in which the coating layer of the composite positive electrode material is replaced by a carbon layer instead of a liquid metal material, that is, step (2) of the preparation method of the composite positive electrode material is:
[0108] The obtained P2-Na 0.67 Ni 0.33 Mn 0.67 O 2 The dispersion was dispersed in ethanol by ultrasonic treatment for 0.5 h. Then, dopamine was added to the dispersion, magnetically stirred at 30 °C for 15 min, and vacuum filtered to obtain P2-Na 0.67 Ni 0.33 Mn 0.67 O 2 @PDA was washed with deionized water and ethanol, dried at 60 °C for 12 h, and then calcined at 550 °C for 10 min in air to obtain P2-Na 0.67 Ni 0.33 Mn 0.67 O 2 @C-PDA; the mass ratio of the carbon layer to the layered transition metal oxide positive electrode material is controlled to remain at 0.05:1;
[0109] Except for the above, other conditions are exactly the same as those in Example 1.
[0110] Application Example 1 and Application Comparative Example 1 respectively provide a positive electrode sheet and a manufacturing method thereof, wherein the manufacturing method comprises:
[0111] The positive electrode materials obtained in the embodiment and the comparative example were respectively mixed with a binder (PVDF) in a mass ratio of 9:1 and dispersed in NMP to prepare a suspension (slurry). The suspension was coated on a current collector aluminum foil and dried in a blast dryer at 60°C for 2 h, and then transferred to a vacuum dryer and dried at 120°C for 12 h to obtain a positive electrode sheet. The specific numbers are shown in Table 1.
[0112] Application Example 2
[0113] This application example provides a positive electrode sheet and a manufacturing method thereof, the manufacturing method comprising:
[0114] The composite positive electrode material obtained in Example 1, the conductive agent (Super-P), and the binder (PVDF) were mixed and dispersed in NMP in a mass ratio of 7:2:1 to prepare a suspension (slurry). The suspension was coated on the current collector aluminum foil and dried in a blast dryer at 60°C for 2 h, and then transferred to a vacuum dryer and dried at 120°C for 12 h to obtain a positive electrode sheet. The specific numbers are shown in Table 1.
[0115] Application Example 3
[0116] This application example provides a sodium ion battery, wherein the sodium ion battery is obtained by slicing the positive electrode sheets obtained in application examples 1 and 2 into a diameter of 11 mm, stacking them with an electrolyte, a separator and a negative electrode sheet in sequence and placing them in a 2032 button battery shell to assemble them into a button battery; the negative electrode sheet is a metal sodium sheet with a diameter of 13 mm, the separator is a glass fiber separator with a diameter of 17 mm, and the electrolyte includes 1M NaClO 4 The battery was dissolved in propylene carbonate and 5% fluoroethylene carbonate (FEC) was added as an additive. The specific number of the obtained battery is shown in Table 1.
[0117] The obtained battery was subjected to charge and discharge tests, and constant current charge and discharge were performed at a voltage range of 2.0 to 4.4 V and a current density of 0.1 C. The first cycle discharge capacity and the discharge capacity after 300 cycles of the battery were tested, and the capacity retention rate was calculated. The specific test results are shown in Table 1.
[0118] Table 1
[0119]
[0120]
[0121] From the test results in Table 1, we can see that:
[0122] The initial discharge specific capacity of the sodium ion battery (battery number 1) including the composite positive electrode material provided in Example 1 is 148.69 mAh·g -1After 300 cycles at 0.1C, the specific capacity is 147.14 mAh g -1 , the capacity retention rate is 98.96%; Figure 1 As shown, by wet coating the layered transition metal oxide positive electrode material with liquid metal material under capillary force, complete coating of primary particles and secondary particles can be formed, and the obtained composite positive electrode material has high initial capacity and capacity retention rate, showing excellent electrochemical performance. Among them, the positive electrode materials provided in Examples 1-10 (obtained battery numbers 1-10) all show significant performance improvement relative to Comparative Example 1 (obtained battery number 11).
[0123] It can be seen that compared with Comparative Example 1, compounding the layered transition metal oxide positive electrode material with the liquid metal material (Examples 1-3) can effectively improve the electrochemical properties of the material. Coating a layer of liquid metal material on the surface of the layered transition metal oxide positive electrode material can greatly improve the structural stability of the material, inhibit its irreversible structural phase change and transition metal ion dissolution under high pressure, interfacial side reactions, etc. The high electrical conductivity of the liquid metal material can also enable the composite positive electrode material to exhibit good rate performance in the absence of a conductive agent. In addition, wet coating is carried out under capillary force, and the resulting suspension has a higher viscosity, which can not only overcome the surface tension of the liquid metal and achieve efficient coating of secondary particles, but also fully coat the primary particles.
[0124] Compared with Example 1, when the polarity difference between the two selected medium solvents is small, the solutions will show a certain miscibility (Example 4), and the capillary bridge built by solvent B is partially destroyed, so that the liquid metal material and the layered transition metal oxide material can only be partially bridged, so that the obtained composite material is unevenly coated and has poor stability. In order to overcome the surface tension of the liquid metal, a solvent with a large polarity difference (high immiscibility) (Examples 1 and 5) is required during the dispersion treatment, so that a high-viscosity "capillary suspension" solution can be obtained, which is manifested as a small amount of solvent B suspended in a large amount of solvent A, connecting the two types of materials through the capillary bridge formed by solvent B, so that the liquid metal layer is better coated on the surface of the layered transition metal oxide positive electrode material.
[0125] Compared with Example 1, the composite positive electrode material with a coating amount within the preferred range shows better initial capacity and capacity retention rate (Examples 6-7); for the composite positive electrode material with a coating content deviating from the optimal coating amount, if the coating amount of the liquid metal material is too little, it will lead to uneven coating and low material conductivity, and the advantages of the coating material cannot be fully exerted (Example 6); if the coating amount of the liquid metal material is too much, it will affect the transmission of sodium ions and make the material kinetic performance lower than the optimal value (Example 7).
[0126] Compared with Example 1, the composite positive electrode material with a volume ratio of solvent A to solvent B within the preferred range exhibits better initial capacity and capacity retention rate (Examples 8-9); if the content of solvent A is too low, solvent B cannot be fully and evenly dispersed in solvent A, which will cause a large amount of layered oxide material and liquid metal material to gather in the solvent B that is not completely dispersed, and the capillary force cannot be fully utilized to complete tight coating (Example 8); if the content of solvent B is too low, the layered oxide material and liquid metal material cannot be fully dispersed in solvent B, resulting in poor coating effect (Example 9).
[0127] Compared with Example 1, the system using only a single solvent containing NMP as a dispersant exhibited poor electrochemical performance (Example 10). This is because the viscosity of the capillary suspension affected by the capillary force is higher, and the capillary bridge formed can form a good interconnected network in the capillary suspension, so that the two types of materials are evenly dispersed in the mixed solvent. In a single solvent, the two types of materials are unevenly dispersed, and the powder migrates unevenly during the solvent evaporation process, and a uniformly coated liquid metal layer cannot be obtained.
[0128] Compared with Example 1, although the traditional carbon coating strategy (Comparative Example 2) can improve the electrochemical properties of the material to a certain extent, its effect is limited. It can only coat the secondary particles and cannot be injected into the gaps between the primary particles. It cannot avoid the generation of cracks between the particles during the charging and discharging process, resulting in structural distortion of the material and poor material stability. In addition, the traditional carbon-coated materials exhibit poor electrochemical properties in the absence of a conductive agent. Compared with the carbon layer coating formed by carbon materials, the coating layer formed by liquid metal materials has higher electrical conductivity, and under capillary force, it can be evenly dispersed to form a highly permeable electronic network with stronger conductivity, which enables the material to have better kinetic properties.
[0129] Compared with the sodium ion battery (battery number 1) containing the positive electrode plate obtained in Application Example 1 of Example 1, the sodium ion battery (battery number 10) containing the positive electrode plate prepared in Application Example 2 according to the ratio of composite positive electrode material, conductive agent (Super-P) and binder (PVDF) of 7:2:1 showed a lower initial capacity due to the lower proportion of active material.
[0130] In summary, the composite positive electrode material provided by the present invention includes a core and a coating layer coated on the surface of the core, wherein the core includes a layered transition metal oxide positive electrode material, and the coating layer includes a liquid metal material. Under capillary force, the liquid metal material with high conductivity is wet-coated onto the surface of the layered transition metal oxide positive electrode material, which can not only achieve efficient coating of secondary particles, but also fully coat primary particles, effectively avoiding the dissolution of transition metal ions and side reactions caused by direct contact between the composite positive electrode material and the electrolyte, and greatly improving the structural stability of the material.
[0131] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0132] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0133] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A composite positive electrode material, characterized in that: The composite positive electrode material comprises a core and a coating layer coating the core, wherein the core comprises a layered transition metal oxide positive electrode material, and the coating layer comprises a liquid metal material.
2. The composite positive electrode material according to claim 1, characterized in that The chemical formula of the layered transition metal oxide positive electrode material is Na x MO2, wherein M includes at least one of Fe, Ni, Co, Mn, and V, and 0<x≤1; Preferably, M is a combination of Ni and Mn, and the chemical formula of the layered transition metal oxide positive electrode material is Na 0.67 Ni 0.33 Mn 0.67 O2; Preferably, the layered transition metal oxide positive electrode material is a P2 phase.
3. The composite positive electrode material according to claim 1 or 2, characterized in that: The liquid metal material includes at least one of nano-scale eutectic gallium indium, gallium indium tin nanoparticles or gallium nanoparticles; Preferably, the mass ratio of the liquid metal material to the layered transition metal oxide positive electrode material is (0.01-0.5):1, preferably (0.03-0.2):
1.
4. A method for preparing the composite positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The layered transition metal oxide material and the liquid metal material are mixed and dispersed in a medium solvent to obtain a composite positive electrode material capillary suspension, the composite positive electrode material capillary suspension is used to form an initial layer on a thin film material, and the film material is pressed to obtain a pressed body, and then the thin film material in the pressed body is peeled off to obtain a composite positive electrode material.
5. The method for preparing a composite positive electrode material according to claim 4, characterized in that: The method for preparing the layered transition metal oxide material comprises: adding a chelating agent to a solution containing a sodium source and an M source to obtain a mixed solution, heating and stirring to obtain a sol, and drying and calcining the sol to obtain the layered transition metal oxide positive electrode material; Preferably, the M source includes at least one of a sulfate, a chloride, an acetate, a nitrate or an oxide of the M element; Preferably, when the M source contains nickel element, the M source comprises a nickel source, and the nickel source comprises at least one of nickel chloride, nickel acetate, nickel nitrate, nickel sulfate or nickel oxide; Preferably, when the M source contains manganese element, the M source includes a manganese source, and the manganese source includes at least one of manganese chloride, manganese acetate, manganese nitrate, manganese sulfate, manganese dioxide, manganese oxalate or potassium permanganate; Preferably, the sodium source comprises at least one of sodium carbonate, sodium acetate, sodium nitrate or sodium hydroxide; Preferably, the dissolving solvent of the solution containing the sodium source and the M source includes at least one of deionized water, ethanol or hydrogen peroxide, preferably deionized water; Preferably, the chelating agent comprises at least one of citric acid, ethylene glycol, and EDTA (ethylenediaminetetraacetic acid), preferably citric acid; Preferably, the amount of the chelating agent and the solution containing the sodium source and the M source is controlled according to the ratio of the molar amount of the chelating agent to the total molar amount of the transition metal (0.5-1.5):1, preferably (0.8-1.2):1; Preferably, the heating temperature is 60-100°C, preferably 70-90°C; Preferably, the stirring includes magnetic stirring and / or mechanical stirring; the rotation speed is 200 to 500 rpm, preferably 300 to 400 rpm; the time is 2 to 6 hours, preferably 3 to 5 hours; Preferably, the drying includes forced air drying and / or vacuum drying; the temperature is 100 to 200° C., preferably 140 to 160° C.; the time is 4 to 8 hours, preferably 5 to 7 hours; Preferably, the calcination comprises: -1 The heating rate is firstly raised to 300-600°C for the first sintering for 4-8h, and then raised to 700-1100°C for the second sintering for 10-20h; Preferably, the calcination comprises heating at 4-6°C·min -1 The heating rate is firstly raised to 400-500°C for the first sintering for 5-7h, and then raised to 850-950°C for the second sintering for 14-16h; Preferably, the calcination atmosphere includes any one of air atmosphere, oxygen atmosphere or argon atmosphere, preferably air atmosphere.
6. The method for preparing a composite positive electrode material according to claim 4 or 5, characterized in that: The preparation method comprises: The medium solvent includes solvent A and solvent B, wherein the polarity indexes of solvent A and solvent B are different and immiscible; the liquid metal material is mixed and dispersed in solvent A, and subjected to water bath ultrasonic treatment to obtain a liquid metal solution; the obtained liquid metal solution and a layered transition metal oxide positive electrode material are mixed and dispersed in solvent B to obtain a capillary suspension of the composite positive electrode material; Preferably, the solvent A and the solvent B have different polarity indices and are immiscible; Preferably, the absolute value of the difference between the polarity index of solvent A and solvent B is ≥5; Preferably, the volume ratio of the solvent A to the solvent B is (6-12):1, preferably (8-10):1; Preferably, the solvent A comprises at least one of dodecane, n-hexane or octanol, preferably dodecane; Preferably, a surfactant is further added to the solvent A, and the surfactant includes AOT, and the surfactant accounts for 0.8% to 1.2% of the mass of the solvent A, preferably 1%; Preferably, the solvent B comprises at least one of methylpyrrolidone, N,N-dimethylformamide or water, preferably methylpyrrolidone; Preferably, the water bath ultrasound treatment time is 0.2 to 0.8 h, preferably 0.4 to 0.6 h; Preferably, the mixing and dispersing device comprises a planetary mixer; Preferably, the mixing and dispersing speed is 100 to 300 rpm, and the mixing and dispersing time is 2 to 6 hours; Preferably, the film material comprises at least one of PET, PE, PP or PPS, preferably PET; Preferably, the pressing temperature is 80-120°C and the pressure is 12-18 MPa; Preferably, the pressed body is cooled first and then the peeling is performed; Preferably, the cooling temperature is 0-10°C and the cooling time is 0.5-2h.
7. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and an active layer disposed on the current collector, wherein the active layer comprises the composite positive electrode material according to any one of claims 1 to 3, and a binder, and does not contain a conductive agent; Preferably, the binder comprises PVDF; Preferably, the mass ratio of the composite positive electrode material to the binder is (8.8-9.2):1, preferably 9:1; Preferably, the current collector comprises aluminum foil.
8. A method for manufacturing a positive electrode sheet according to claim 7, characterized in that: The manufacturing method comprises: mixing the composite positive electrode material, a binder and a pulping solvent to obtain a slurry, coating the obtained slurry on a current collector, and slicing after drying to obtain a positive electrode sheet; Preferably, the pulping solvent comprises NMP; Preferably, the drying comprises drying in a forced air dryer at 40 to 80° C. for 1 to 3 hours, and then transferring to a vacuum dryer and drying at 100 to 140° C. for 8 to 16 hours; Preferably, the mass loading of the composite cathode material on the current collector is 1.5-1.8 mg / cm 2 .
9. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 7, as well as an electrolyte, a separator and a negative electrode sheet; Preferably, the diameter of the positive electrode plate is 10-12 mm; Preferably, the electrolyte comprises 1M NaClO4 dissolved in propylene carbonate, and 4% to 6% fluoroethylene carbonate is added as an additive; Preferably, the diaphragm comprises a glass fiber diaphragm; the diameter of the diaphragm is 16 to 18 mm; Preferably, the negative electrode plate comprises a metallic sodium negative electrode plate; the diameter of the negative electrode plate is 12 to 14 mm.
10. A power device, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Cited By
Liquid metal for liquid cooling line cooling liquid
CN120350422A